Thermal Processing of Packaged Foods - Holdsworth, S. Donald; Simpson, Ricardo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This new edition discusses the physical and engineering aspects of the thermal processing of packaged foods and examines the methods which have been used to establish the time and temperature of processes suitable to achieve adequate sterilization or pasteurization of the packaged food. The third edition is totally renewed and updated, including new concepts and areas that are relevant for thermal food processing: This edition is formed by 22 chapters-arranged in five parts-that maintain great parts of the first and second editions The First part includes five chapters analyzing different topics associated to heat transfer mechanism during canning process, kinetic of microbial death, sterilization criteria and safety aspect of thermal processing. The second part, entitled ThermalFood Process Evaluation Techniques, includes six chapters and discusses the main process evaluation techniques. The third part includes six chapters treating subjects related with pressure in containers, simultaneous sterilization and thermal food processing equipment. The fourth part includes four chapters including computational fluid dynamics and multi-objective optimization. The fifth part, entitled Innovative Thermal Food Processing, includes a chapter focused on two innovative processes used for food sterilization such high pressure with thermal sterilization and ohmic heating. Thermal Processing of Pack aged Foods, Third Edition intended for a broad audience, from undergraduate to post graduate students, scientists, engineers and professionals working for the food industry.
Preface First Edition -- Preface Second Edition -- Foreword Third Edition -- Part I. Fundamentals of Thermal Food Processing -- 1. Introduction -- 2. Heat Transfer -- 3. Kinetics of Thermal Processing -- 4. Sterilization, Pasteurization and Cooking Criteria -- 5. Safety Aspects of Thermal Processing -- Part II. Thermal Food Process Evaluation Techniques -- 6. Heat Penetration in Packaged Foods -- 7. The General Method and Its Applications -- 8. Formula Methods and Analytical Techniques -- 9. Some Factors Affecting F-Values and Mass-Average Sterilizing Values -- 10. Microbiological Methods -- 11. Software for Thermal Food Processing Evaluation and Optimization -- Part III. Engineering Aspects of Thermal Food Processing -- 12. Pressures in Containers -- 13. Mechanical Agitation and Rotation of Cans -- 14. Simultaneous Sterilization -- 15. Total and Transient Energy Consumption in Batch Retort Processing -- 16. Batch Processing, Retort Scheduling and Optimizing Plant Production -- 17. Thermal Food Processing Equipment -- Part IV. Mathematical Modeling, Simulation, Optimization, Control and Automation -- 18. Computational Fluid Dynamics in Thermal Food Processing -- 19. Optimization of Thermal Food Processing -- 20. Multiobjective Optimization in Thermal Food Processing -- 21. Process Instrumentation, Online Control and Plant Automation -- Part V. Innovative Thermal Food Processing -- 22. High-Pressure Thermal Sterilization (HPTS) and Ohmic Heating (OH) Applied to Thermal Food Processing -- Index.
Keywords: Food science; Food Science